A remotely accessible solar tracker system design - Çınar, Said Mahmut; Hocaoğlu, Fatih Onur; Orhun, Murat (AIP Publishing, 2014)
In this paper, a new solar tracking system designed and constructed at Afyon Kocatepe University to maximize the efficiencies of different photovoltaic (PV) panels is proposed. The system is composed of two main parts: first is the mechanical part, whereas the second is the control part. The mechanical part of the system has the ability to move both in vertical and in horizontal axes. Servo engines are selected and used at this part. On the other hand, control part is designed as to be achieved via remote access. The control strategy of the system should easily be altered when desired. This enabled us to test different control algorithms. Moreover, different PV panels produced by different technologies are tested on the system. Electricity generation outputs of PV panels obtained from the tracking system are compared with outputs of fixed ones. Finally comparison results of different control strategies are presented and discussed.
Keywords: PV Panels; Remotely Accessible; Solar Tracker; 7. Clean energy; 6. Clean water